KARAKTERISTIK DAN TINGKAT KEPATUHAN MINUM OBAT ANTI HIPERTENSI PADA PASIEN HIPERTENSI DI PUSKESMAS AIR BESAR - Daniel Sinaga; Irwan Irwan; Samuel Maruanaya; Presli G Siahaya (PAMERI, 2022)
Hypertension known widely as a cardiovascular disease in which patients has a blood pressure above normal. Treatments on hypertension can be fully completed when a few factors are met. One of the factors mentioned is hypertension drug adherence. This study is conducted to know characteristics on hypertension drugs adherence patients in Puskesmas Air Besar. This study is an observational research is a descriptive cross-sectional study. The sample in this study is hypertension patients in Puskesmas Air Besar Desa Batu Merah in 2021, 108 patients, will be given a questionnaire to fill. The data then taken and analyzed using univariate approach. This study shows that in Puskesmas Air Besar Desa Batu Merah most patients are in the range of 45-54 of age which are 31 patients (28,78%), most patients as many as 80 patients (74,07%) are female, most patients as many as 52 patients (48,15%) are on low level of education category, most patients as many as 46 patients (42,60%) are housewife, most patients as many as 25 patients (23,15%) does not have any family history for hypertension, most patients as many as 101 patients (93,52%) does not smoke, most patients as many as 67 patients (62,04%) found in this study are mostly obese, and most patients found in this study as many as 68 patients (62,96%) has low category on adherence level.